SINERGITAS TNI DENGAN PEMANGKU KEPENTINGAN TERKAIT DALAM KEBIJAKAN DERADIKALISASI DI WILAYAH PROPINSI JAWA TIMUR - Wibisono Poespitohadi; Wahyu Wiyani; Singgih Pambudi Arinto; Titot Edy Suroso; Priyo Dari Mulyo; Lian Agustina (Media Bina Ilmiah, 2023)
The rise of radicalism means that the situation and cases and issues trigger horizontal and vertical conflicts so that they become a threat to the country's defense. This study focuses on the threat of radicalism in East Java Province, one of the provinces with a relatively high level of radicalism. The implementation of the deradicalization program carried out by the TNI and Polri and other elements is currently only limited to the recipient level, and is impossible to implement at the frontline unit level, such as at the Koramil, Babinsa or Babinkamtibmas Police Station levels. The purpose of this study is to analyze the synergy between the TNI and related stakeholders in deradicalization in the East Java province. The research was conducted using qualitative methods and data collection was carried out through interviews and document studies. The results of the study show that the synergy between the TNI and deradicalization actors in East Java Province is generally successful but not optimal. The conclusion of the study is that the communication perspective in disseminating information and planning anti-radicalism actions has not been optimal; Coordination of anti-radicalization and deradicalization programs was not carried out optimally. and BNPT synergy that has not yet applied to other agencies such as the TNI, Polri, religious leaders and others. The study aims to create a roadmap for understanding and harmony in combating radicalism among relevant stakeholders and provide budgetary support and add personnel to combat the threat of radicalism.